Duration and Sociodemographic Factors Associated with Exclusive Breastfeeding Among Mothers in Urban and Semi-Rural Areas of Libreville and Lambaréné in Gabon - Minto'o, Steeve; Loembe, Fifi Claire; Larissa, Midili Thècle; Pemba, Mireille Mensan; Raïssa, Koumba Maniaga; Mimbila-Mayi, Mylène; Nzame, Yolande; Murielle, Essomo; Kuissi-Kamgaing, Eliane; Koko, Jean; Ategbo, Simon (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Exclusive breastfeeding from birth to six months of age has an unparalleled benefit on a child's growth and development. This survey aimed to assess the practice of exclusive breastfeeding (EBF) in Libreville and Lambaréné. Method: This is a prospective study, including mother-child pairs of infants taken to vaccination centers in Libreville (urban area) and Lambaréné (semi-rural area). The data collected included sociodemographic aspects of families, the children's characteristics, and the duration of EBF in months. Result: We included 552 mother-child pairs, 58% of whom were recruited (n = 320) in Libreville. The average age of mothers was 26.5 ± 6.4 years, while fathers were 33.3 ± 7.8 years. The mean age of children was 4.2 ± 3.1 months. Male participants were accounted for 52.2% (n = 288), while females 47.8% (n = 264). The mean duration of exclusive breastfeeding in the whole was 0.9 months. Six-month EBF was generally performed at 9.2% (n = 51,  95% CI = 7.1%-11.9%). The factors influencing the EBF were father’s level of education (all classes combined) (p = 0.025), marital status (p = 0.011), and residential area (OR = 3.40, p <0.001) Conclusion: The duration of exclusive breastfeeding in the two studied is lower than the WHO recommendations. The associated factors found are areas of work to be explored to encourage this important practice for our infants.